Leveraging Asymmetric Relations in Sister City Relationships - Stivani Ismawira Sinambela; Faris Al-Fadhat; Takdir Ali Mukti; Tulus Warsito (Andalas Institute of International Studies UNAND, 2025)
This research analyzes the Sister City collaboration model that influences the success of economic cooperation between local governments. Sister City Relationship (SCR) is a form of subnational diplomacy that connects cities across countries through formal agreements, aiming to promote economic, cultural, and social cooperation. However, many SCR initiatives remain symbolic and fail to generate tangible benefits. This study proposes a more strategic approach by examining how asymmetry between cities can enhance economic cooperation. The theoretical framework adopts an asymmetric approach, arguing that mutual compatibility can emerge from unequal relationships. Compatibility is operationalized through indicators such as: (1) Area, (2) Gross Domestic Products (GDP) and (3) Human Development Index (HDI), which reflect the economic and developmental capacity of a city or region. A coupling model is used to categorize relationships into Big-Small and Small-Big pairings, referring respectively to partnerships where a big Local Cities collaborates with a smaller Foreign Cities, and vice versa. These asymmetric configurations are found to be more effective than symmetrical pairings, which often struggle with overlapping interests and lack of reciprocity. Empirical findings based on selected SCR cases in Indonesia such as Bandung, Surabaya and Medan, shows that coupling cities with complementary resources, rather than equal status, enables more dynamic and outcome-driven engagements. The study offers both theoretical and practical contribution for designing more strategic and resource-based asymmetric relations.